Forecasting Rice Harvest Area in Jombang Regency with Triple Exponential Smoothing Method - Hariri, Rifan (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Currently, the conversion of agricultural land is a serious problem that occurs in every region, including in Jombang Regency. Land conversion has various impacts, including a decrease in farmers' income and even farmers are threatened with losing their livelihoods. The purpose of this research is to forecast or predict the harvest area of rice plants in Jombang Regency. The data used in this research is secondary data from the Central Bureau of Statistics of Jombang Regency in 2025. Data analysis uses the triple exponential smoothing forecasting method. The forecasting results show that the harvest area of food crops in the form of rice in the Jombang Regency area in 2025 starting from quarter 1 (Q1) to quarter 3 (Q3) has decreased significantly. The highest harvest area was in quarter 1 (Q1) amounting to 27,304.43 Ha and the lowest rice harvest area was in quarter 3 (Q3) with a harvest area of 10,675.47 Ha.